Pharmacist-led remote follow-up service for non-metastatic breast cancer patients: a prospective randomised controlled trial of pharmaceutical intervention - Wu, Miaohui; Huang, Xiaoyan; Liang, Cuilv; Wang, Peihong; Zhang, Yalan; Zhang, Yin (Frontiers in Pharmacology, 2025)
BackgroundNon-metastatic breast cancer accounts for 87.8% of breast cancer cases. However, the high risk of drug adverse drug reactions due to multiple combined medications, along with the urgent need for out-of-hospital medication adherence and management, poses substantial challenges. Traditional treatments often fail to meet the full-cycle management needs of patients. Remote pharmaceutical follow-up, as an emerging model, may address these issues. This study aimed to investigate the intervention effect of remote pharmaceutical services via a follow-up app on non-metastatic breast cancer patients.MethodsFrom May 2023 to March 2025, 178 patients with non-metastatic breast cancer were enrolled and randomly assigned to an intervention group (receiving remote pharmaceutical follow-up via an app) or a control group (receiving only routine treatment), with a 6-month follow-up period. The primary outcome was the incidence of severe adverse drug reactions, while secondary outcomes included medication adherence scores, pharmaceutical knowledge scores, and quality of life assessments.ResultsThe incidence of severe adverse drug reactions in the intervention group (20.2%) was significantly lower than that in the control group (50.0%, P < 0.01), with notable improvements particularly in non-hematological adverse drug reactions. The intervention group also demonstrated significantly higher pharmaceutical knowledge scores and medication adherence scores compared to the control group (P < 0.05). In terms of quality of life, the intervention group showed greater improvements in symptom scores and overall composite scores (P < 0.01), with faster recovery of global health and functional scores in the late follow-up phase.ConclusionRemote pharmaceutical services delivered via a follow-up app effectively reduce the incidence of severe adverse drug reactions and improve medication knowledge, adherence, and quality of life in non-metastatic breast cancer patients. This model provides a viable new approach for out-of-hospital management and highlights the value of pharmacists in the full-cycle management of oncology care. Future research should further explore preventive strategies for hematological adverse drug reactions and extend the follow-up period to refine the clinical application of this management model.